2017
DOI: 10.1080/15513815.2017.1315199
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in the Clinical Manifestations of Childhood Asthma

Abstract: The main findings that TSE-induced oxidative stress is a risk for intermittent asthma and eczema may be clinically significant for the disease prevention and therapeutic improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Moreover, it was shown that toxic chemicals in tobacco smoke are able to induce epigenetic changes with increased expression of various pro-inflammatory genes (57). Therefore, prenatal and postnatal exclusion of tobacco smoke exposure could be used as an important preventive approach against allergic sensitization and inflammation development with the attenuation of oxidative stress (58). Prenatal supplementation of vitamin C and E improved pulmonary functions of newborns of smoking mothers (59), but in a large placebo-controlled study, this effect was not confirmed (60).…”
Section: Antioxidant Strategies For Asthma Treatmentmentioning
confidence: 99%
“…Moreover, it was shown that toxic chemicals in tobacco smoke are able to induce epigenetic changes with increased expression of various pro-inflammatory genes (57). Therefore, prenatal and postnatal exclusion of tobacco smoke exposure could be used as an important preventive approach against allergic sensitization and inflammation development with the attenuation of oxidative stress (58). Prenatal supplementation of vitamin C and E improved pulmonary functions of newborns of smoking mothers (59), but in a large placebo-controlled study, this effect was not confirmed (60).…”
Section: Antioxidant Strategies For Asthma Treatmentmentioning
confidence: 99%
“…10,11 Urinary concentrations of adenosine have been measured in healthy children, 12,13 and few patients with miscellaneous conditions such as inherited metabolic disorders, cardiomyopathy, and respiratory failure. 13 Urinary measurements of 8-OxodG have been conducted in healthy children, 14 contemporary patients with cystic fibrosis, 15 and subjects exposed to environmental pollutants, 16,17 including asthmatic patients exposed to tobacco smoke. 17 Whereas some knowledge of FE NO and partitioned-NO is available in relation with EIB, no information exists on the role of urinary purine metabolites in assessing EIB in asthmatic children.…”
mentioning
confidence: 99%
“…13 Urinary measurements of 8-OxodG have been conducted in healthy children, 14 contemporary patients with cystic fibrosis, 15 and subjects exposed to environmental pollutants, 16,17 including asthmatic patients exposed to tobacco smoke. 17 Whereas some knowledge of FE NO and partitioned-NO is available in relation with EIB, no information exists on the role of urinary purine metabolites in assessing EIB in asthmatic children.…”
mentioning
confidence: 99%
“…Besides inflammation in the airways, bronchoconstriction may also be triggered by various types of proteolytic and oxidative damage. Therefore, it is argued that anti-inflammatory and anti-oxidant agents will prevent the triggering of bronchoconstriction which constitutes the fundamental mechanism in asthma (4,6,9,12). It has been reported that zinc, which has anti-oxidant, anti-apoptotic, anti-inflammatory and anti-allergic properties, is important in dermatologic and respiratory diseases, while zinc deficiency plays an important role in the pathogenesis and severity of dermatologic and respiratory diseases (2,8,11).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies also showed that bronchoconstriction is triggered by proteolytic and oxidative damage in the airway epithelium in addition to airway inflammation (2,4). The airway epithelium may be affected by oxidative damage caused by inflammatory cells and oxidant agents in the air (5,6). Zinc is an essential dietary factor which has anti-inflammatory and anti-oxidant properties, and it is found in the contents of numerous cells of human body and structures of various enzymes (e.g.…”
Section: Introductionmentioning
confidence: 99%